Impact of Menopause Counselling on Maternal Anxiety in Gebyog Village, Magetan, Indonesia - Chotijah, Putri Indriyani Renti; Hanifah, Astin Nur; Handayani, Tinuk Hesti; Suparji, Suparji (Health Dynamics, 2024)
Background: Menopause signifies the end of menstruation and ovarian follicle activity in women. It is diagnosed after 12 consecutive months of amenorrhea without other causes. Typically occurring between 40 and 50 years, menopause often induces anxiety, especially among women with limited knowledge. To address this, the government promotes health counseling to improve women's understanding and management of menopause. Methods: This study utilized a pre-experimental design involving 63 respondents fromGebyog Village, Magetan, Indonesia, selected by simple random sampling. The study examined two variables: the independent variable (counseling) and the dependent variable (anxiety level). Data was collected using the Hamilton Rating Scale for Anxiety (HARS) questionnaire, administered both before and after counseling sessions. Descriptive analysis was conducted using frequency distribution, and the Mann-Whitney U test was used for inferential analysis. Results: The counseling intervention led to a significant reduction in anxiety levels among the participants. The Mann-Whitney U test results indicated a P value of 0.000, demonstrating a statistically significant effect of counseling on reducing anxiety levels (P = 0.000 < α = 0.05). Conclusion: Counseling effectively reduces anxiety in women facing menopause. It is recommended that health workers enhance their efforts in providing menopause-related counseling, particularly through village health posts like posbindu and poslansia, to support women during this transition.